Varietates topiorum Perspektive und Raumerfassung in Landschafts- und Panoramabildern der römischen Wandmalerei vom 1. Jh. v. Chr. bis zum Ende der pompejanischen Stile - Hinterhöller-Klein, Monika (Phoibos Verlag, 2015)
The purpose and subject of this dissertation is an analysis in space-representation and perspective drawing of Roman and Campanian landscape painting to develop and reconstruct the modes of landscape recognition and spatial perception structures in the late Republic and early Empire. This aim is realized with the help of interdisciplinary methods, as the possibilities, limits and developments of perspective representation are studied on the basis of descriptive geometry, its terminology and theoretical background.